Hepatoprotective Effect of Ethanolic Leaves Extract of Musa Paradisiaca on CCL4-Induced Hepatotoxicity in Albino Rats - Goje, Lazarus J.; Abdulkadir, Maryam U.; Hammari, Abubakar M.; Adam, Ibrahim A.; Abubakar, Adamu J.; Mamman, Kudih N.; Haruna, Abu-ubaida; Muhammad, Abdullahi (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Musa paradisiaca (banana) leaves have been extensively used in traditional medicine for the treatment and management of disorders related to oxidative stress, including diabetes, neurodegenerative diseases, and cancer. However, there is limited scientific evidence supporting these claims. This study aimed to evaluate the hepatoprotective and antioxidant properties of Musa paradisiaca leaf extract in albino rats with carbon tetrachloride (CCl₄)-induced liver damage. Fresh leaves of Musa paradisiaca were collected, shade-dried, and extracted using 60% ethanol. Thirty albino rats were randomly assigned to five groups: control, CCl₄-induced, CCl₄ + silymarin (100 mg/kg), CCl₄ + Musa paradisiaca extract (200 mg/kg), and CCl₄ + Musa paradisiaca extract (400 mg/kg). The extract was administered orally, while CCl₄ was given intraperitoneally (IP) to induce liver damage. Phytochemical screening of the extract revealed the presence of alkaloids, saponins, tannins, flavonoids, anthraquinones, and steroids. Liver function biomarkers—alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP)—were analyzed spectrophotometrically. The results indicated that the Musa paradisiaca extract significantly reduced ALT, AST, and ALP levels (p ≤ 0.05) compared to the CCl₄-treated group, demonstrating its hepatoprotective effects. The 400 mg/kg dose exhibited a more pronounced effect, comparable to that of silymarin. These findings provide scientific validation for the traditional use of Musa paradisiaca leaves in managing liver disorders and conditions associated with oxidative stress. Further studies are recommended to isolate and characterize the bioactive compounds responsible for these effects.